(untitled) (Proceedings of International Educators Conference, 2024)
The article presents the results of the evaluation of modern sensitivity indicators to antifungal preparations in 1052 strains of Candida species isolated from patients with urogenital candidiasis in the period from 2010 to 2015. Pathogen culture identified was examined to determine the sensitivity to amphotericin В, 5-fluorocytosine, fluconazole, itraconazole, ketoconazole, and miconazole. At present, along with a predominance of Candida albicans, the etiological range of causative agents of urogenital candidiasis is characterized by an increasing proportion of non-albicans species (Candida glabrata, Candida krusei, Candida parapsilosis). Heterogeneous specific structure of the disease and increase in resistance rates of Candida to commonly used azole antifungals (fluconazole, itraconazole, miconazole) necessitate permanent monitoring of the sensitivity of infectious agents to antifungals and optimizing treatment regimens based on these indicators.